INTEGRATION OF MADRASAH DINIYAH AS STRENGTHENING RELIGIOUS MODERATION IN ELEMENTARY SCHOOL - Muhammad Fatchur Rochim,; Siti Khumairotul Lutfiyah,; Iksan Kamil Sahri, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract The purpose of this research is to identify the cultivation of religious moderation in the learning process applied by Madrasah Diniyah teachers. This research comprehensively explains how Madrasah Diniyah integration is implemented in elementary schools and how it strengthens religious moderation in the school environment. This study uses a qualitative approach, with data collection methods including observation, interviews, documentation, and analysis using the Miles and Huberman model. The results show that the integration of Madrasah Diniyah at Khazanah Ilmu Sidoarjo Elementary School effectively increases students' religious knowledge, emphasizing important religious activities as part of a strategy to strengthen religious moderation. The efforts to cultivate religious moderation in the learning process are through Madrasah Diniyah teachers at Khazanah Ilmu Sidoarjo, who more often instill an attitude of compassion and love of peace in the learning process.